FACTORS THAT INFLUENCE THE COMPLIANCE OF ANTIRETROVIRAL THERAPY (ART) ON HIV / AIDS PATIENTS IN DR. SARDJITO YOGYAKARTA - Akbar Satria Fitriawan; Khudazi Aulawi; Haryani Haryani (Journal of Nursing Science Update (JNSU), 2019)
Antiretroviral therapy (HAART) is very important for patients with HIV/AIDS in order to prevent the appearance of AIDS symptoms, reduce hospitalizations and prevent mortality. But it required minimum of 95% adherence rate to prevent the occurrence of viral resistance to and AIDS development. Identification of the factors that influence adherence are needed to develop appropriate interventions to maintain patient adherence. The aimed of the study was to assess adherence rate with antiretroviral therapy in HIV-infected patients in Dr.Sardjito General Hospital and identify factors that influence it. Observational analytic study with cross sectional design was used in this study. The independent variable in this study is sociodemographic factors, social support, depression, self efficacy, quality of health care provider’s communication and patient's CD4 count. Bivariate and logistic regression is used to determine the factors that affecting adherence. A total of 64 HIV/AIDS patients participated in this study. 36 patients (56.3%) had adherence <95% with an average adherence of 83.64% (SD = 21.25). Depression, social support, self efficacy, quality of health care provider’s communication, age and employment status is associated with adherence (p <0.05). In multivariate analysis, low self-efficacy (PR = 12,94; p = 0,001) and low social support (PR = 5,47; p = 0,024) is a predictor of poor medication adherence. In conclusion self efficacy and social support is a predictor of adherence in HIV/AIDS patient. Interventions that focus on these factors is expected to improve patient adherence to medication.